(untitled) (Journal of history-rus, 2023)
The content of the article stems from the need for an in-depth study of the data covering the Balkan Wars in the Ottoman Empire published under the heading "Foreign News" of the Kazakh newspaper in 1912-1913. The main objective of the research is to scientifically reveal the history of Kazakh-Turkish political and cultural relations in the early 20th century, based on the data published in the newspaper "Kazak". In this regard, the article reviews and systematises the information on the Balkan wars between the Ottoman Empire and Bulgaria, Montenegro, Serbia and Greece, summarises with concrete examples the attitude of the national intelligentsia to the war in the Ottoman Empire, which was published in the edition of the newspaper "Kazak", covers the news of the newspaper on the Balkan wars, information on the topic of the war in relation to the Kazakh steppe is considered a novelty. In the development of the subject idea was guided by the principle of evaluation of historical events and phenomena from the point of view of national interests. As a result, comprehensive documentary information on Kazakh-Turkish relations was compiled from the issues of the newspaper "Kazak" published between 1913-1918. As a result of the research, the Balkan War in the Ottoman Empire, the results of the struggle for power during the I-II Balkan War period published in the Kazak Newspaper were analysed and scientific conclusions were drawn based on the data obtained from the National Publication. The main source is the edition of the Kazakh newspaper.